The Effects of the Minimum Wage in the Formal and Informal Sectors in Brazil - Sara Lemos (Institute for the Study of Labor (IZA), 2004)
The minimum wage literature is very limited on empirical evidence for developing countries. This already limited literature is even more limited on the effects of the minimum wage in the informal sector, where most of the poor are. Extending the understanding of minimum wage effects both in developing countries and in particular in the informal sector is crucial if the minimum wage is to be used as a policy to help poor people in poor countries. This paper estimates wage and employment effects, accounting for sorting into the formal and informal sectors. The data used is a monthly Brazilian household survey from 1982 to 2000 at individual and regional levels. The formal and informal sectors employment effects were both found to be negative, consistent with the presence of a large spike, substantial spillover effects, and the associated compression effect in the wage distribution of both sectors. This suggests a downwards sloping labour demand curve in both sectors, challenging the standard Two Sectors Model as inadequate to explain the effect of the minimum wage on the formal and informal sectors in Brazil and in Latin America more generally.
Keywords: J38; 330; minimum wage; wage effect; employment effect; informal sector; Brazil; Mindestlohn; Lohn; Beschäftigungseffekt; Informeller Sektor; Schätzung; Brasilien